Pengaruh Hutang Dan Pembagian Dividen Terhadap Harga Saham Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Tri Suci Rahmayanti; Hendry Saladin; Totok Sudiyanto (Universitas PGRI Palembang, 2022)
ABSTRACTThe purpose of this study is to determine the impact of debt and the overall dividend distribution on stock prices using the variable debt to equity ratio, dividend payout ratio and closing stock price in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study used quantitative methods The population in this study was 26 companies. The purpose of this study is to determine the impact of debt and the overall dividend distribution on stock prices using the variable debt to equity ratio, dividend payout ratio and closing stock price in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This study used quantitative methods The population in this study was 26 companies. The technique was chosen for sampling using purposive sampling techniques so that a sample of 9 companies was obtained during the 2017-2020 period. This research was conducted using quantitative methods. Data analysis techniques using the kolmogrov smirnov one-sample normality test, multicolonierity test using variance inflation factor (VIF) and Tollerance, autocorrelation test using durbin-watson and heterokedasticity test using scatterplots. Meanwhile, test the hypothesis using multiple linear analysis tests. The results of the hypothesis test concluded that partially the debt to equity ratio had a significant effect on the stock price with a significant value smaller than 0.05 (0.001 < 0.05). And the dividend payout ratio has a significant effect on the share price of a food and beverage subsector manufacturing company with a significant value smaller than 0.05 (0.016 < 0.05). Meanwhile, simultaneously there is a significant influence on the variable debt to equity ratio and dividend payout ratio on the stock price with a significance value smaller than 0.05 (0.001 < 0.05). Keywords: debt to equity ratio, dividend payout ratio and stock price ABSTRAK Tujuan penelitian ini ialah mengetahui dampak hutang dan pembagian dividen secara keseluruhan terhadap harga saham menggunakan variabel debt to equity ratio, dividend payout ratio serta harga saham penutup pada perusahaan manufaktur subsektor makanan dan minuman yang terdaftar di Bursa Efek Indonesia periode 2017-2020. Penelitian ini memakai metode kuantitatif Populasi dengan data sebanyak 26 perusahaan. Teknik dipilih untuk penentuan sampel menggunakan teknik purposive sampling sehingga diperoleh sampel sebanyak 9 perusahaan selama periode 2017-2020. Penelitian ini dilakukan dengan menggunakan metode kuantitatif. Teknik analisa data menggunakan uji normalitas one-sample kolmogrov smirnov, uji multikolonieritas menggunakan variance inflation factor (VIF) dan Tollerance, uji autokorelasi memakai durbin-watson dan uji heterokedastisitas menggunakan scatterplots. Sedangkan, uji hipotesis menggunakan uji analisis linier berganda. Hasil uji hipotesis menyimpulkan bahwa secara parsial debt to equity ratio memiliki pengaruh yang signifikan terhadap harga saham dengan nilai signifikan lebih kecil dari 0,05 ( 0,001 < 0,05 ). Dan dividend payout ratio berpengaruh siginifikan atas harga saham pada perusahaan manufaktur subsector makanan dan minuman dengan nilai signifikan lebih kecil dari 0,05 ( 0,016 < 0,05 ). Sedangkan, secara simultan terjadinya pengaruh signifikan pada variabel debt to equity ratio dan dividend payout ratio atas harga saham dengan nilai signifikansi lebih kecil dari 0,05 ( 0,001 < 0,05 ). Kata kunci : debt to equity ratio, dividend payout ratio, harga saham